92. Brainstem reflexes: New tools for differential diagnosis between idiopathic and psychogenic cervical dystonia?. Issue 4 (April 2016) - Briscese, L.; Carboncini, M.C.; Barloscio, D.; Crecchi, A.; Parenti, L.; Mazzucchi, S.; Rossi, B.; Sartucci, F.; Bocci, T.
Abstract : Cervical idiopathic dystonia (CID) is the most common kind of primary dystonia, but its pathogenesis remains still unclear. As in other movement disorders, the major challenge is to recognize the organic from the psychogenic phenotype. Our objective was to evaluate the reliability of blink reflex test (BRT) in detecting powerful differences in patients with diagnosis of CID or (clinically presumed) psychogenic dystonia (PD). Twelve subjects were enrolled (6 CID, 6 PD), and BRT was assessed in term of R1 and R2 latencies and habituation phenomenon (trains of 10 stimulus, 1 Hz of frequency, 200 ms of duration). Electrodes were placed over the orbicular inferior muscle (recording electrode) and lateral canthus (reference). CID patients showed both an enhanced latency of polysynaptic R2 responses and a lack of habituation compared with subjects diagnosed as PD ( t -test: p  < 0.001). Our results support the hypothesis of a dysfunction of brainstem reflex circuits on the basis of CID. As in Parkinson Disease, one could speculate that this phenomenon relies on changes in the inhibitory drive from basal ganglia output structures, via tecto-reticular projections, to the superior colliculus.